(untitled) (AYUSHDHARA, 2024)
Background: Spondylolisthesis refers to the forward, sideways, or backward movement of one vertebral body over another. Mechanical low back pain is especially linked to jobs that require heavy lifting, bending or twisting, such as manual work and extended periods of driving. Spondylolisthesis is one of the mechanical factors contributing to low back pain. “Degenerative spondylolisthesis is most common in adults, with risk increasing as age progresses.” In the Indian population, the incidence of low back pain has reported to range from 6.2% (in the general population) and 92% (in construction workers). “Lumbar spondylolisthesis can be compared to Grdhrasi in Ayurveda due to similar clinical features.” It is included under Vataja nanatmaja vyadhi. This case study explores Ayurvedic management and outcomes in a 68-year-old female patient with severe low back pain and stiffness. Methods: Assessment parameters included symptoms grading scores of range of movement, posture, and pain, functional scores such as the Oswestry Disability Questionnaire, and changes in MRI grading. Management included Vata hara and Brimhana measures such as Kati vasti, Abhyanga, Nadisweda, Matra vasti, Tiktaksheeravasti, Patrapottali pinda sweda, Ksheeravaitarana vasti, and Salvana upanaha, along with some disease palliative medications for two months with a break in between. Results and conclusion: The patient showed improvement in subjective symptoms, rating scales, and MRI findings, shifting from grade 2 to grade 1 spondylolisthesis.